The Influence of the Literacy Movement on the Learning Motivation and Activeness of Elementary School Students - Zulfikar, Zulfikar; Asiz, Sitti Aida; Haslindah, Hasilndah (Institut Agama Islam Negeri Palopo, 2023)
This study aims to analyze the influence of literacy movement program on students' learning interest and activity in learning. The research involved 60 elementary school students in Cluster I of Wajo District, Makassar City. The researcher used an ex-post facto design to reveal the influence of the literacy movement program on students' learning interest and activity without changing or manipulating the variables or samples. Data collection was conducted using questionnaire and observation techniques. The questionnaire was given to students to obtain data on the application of literacy movement and students' interest, while observation was carried out to obtain data on students' activity in the learning process with literacy movement. The collected data were then analyzed descriptively and inferentially. The results of the study revealed that the literacy movement program can help improve students' interest in learning and reading, help students acquire new skills in reading, writing, and speaking, and can significantly increase students' participation in learning activities.